Stable isotope record of benthic foraminifera in late Pleistocene sediments - Oppo, Delia W; Fairbanks, Richard G; Gordon, Arnold L; Shackleton, Nicholas J (Supplement to: Oppo, DW et al. (1990): Late Pleistocene Southern Ocean d13C variability. Paleoceanography, 5(1), 43-54, https://doi.org/10.1029/PA005i001p00043, 1990)
Variations in the contribution of North Atlantic Deep Water (NADW), relative to North Pacific Deep Water (NPDW), to the Southern Ocean, are assessed by comparing delta13C records from the mid-depth North Atlantic, deep Southern Ocean, and deep equatorial Pacific Ocean. In general, the relative contribution of NADW was greater during interglaciations than glaciations of the past 550,000 years. An increase in the NADW flux to the Southern Ocean since the last glaciation was proposed to have resulted in higher atmospheric CO2 in the Holocene (Broecker and Peng, 1989, doi:10.1029/GB003i003p00215). Glacial-interglacial variations in the proportion of NADW in the Southern Ocean may have also influenced atmospheric CO2 levels over the past 550,000 years. The greatest relative flux of NADW to the Southern Ocean occurred during interglacial stage 11. Faunal data suggest that the North Atlantic polar front and southern Indian Ocean subtropical convergence zone were located farthest poleward during stage 11. Warmth in these locations and a strong southward flux of NADW during stage 11 may be causally linked by the NADW formation process/warm water return route (Gordon, 1986, doi:10.1029/JC091iC04p05037). Time series analysis indicates that delta13C variations in the deep Southern Ocean occur at the same frequencies as the Earth's orbital variations and are coherent and in phase with delta18O. At most, 50% of the glacial-interglacial delta13C amplitude in the Southern Ocean is due changes in the contribution of NADW. The remainder is probably due to mean ocean delta13C changes.